Laparoscopic Heminephrectomy for Duplex Kidney in Children—The Learning Curve - Polok, Marcin; Dzielendziak, Agata; Apoznanski, Wojciech; Patkowski, Dariusz (Frontiers in Pediatrics, 2019)
Objectives: Outcomes evolution during the learning curve of laparoscopic transperitoneal heminephrectomy in children with a duplex kidney. Materials and Methods: The data of 33 children, operated on between 2008 and 2017, with complicated duplex kidney, were subjected to a retrospective analysis. All patients were operated on by transperitoneal access using the laparoscopic technique. Patients were divided into two groups (1: subsequent operation 1–16, and 2: operations 17–33) to evaluate the learning curve. Results: There was no need for conversion. Total complications occurred in seven patients in Group 1 and 2 patients of Group 2 (p < 0.05). Two patients (6%) (both upper pole heminephrectomies) required reoperation to remove the ureter stump because of recurrent UTIs due to undiagnosed VUR to the stump (1 from each of Groups 1 and 2). Prolonged urine leakage (over 4 days) was observed in four patients (12%; all from group 1); in three patients, conservative treatment was successful, while the placement of a DJ catheter was needed in the fourth. A significant decrease of kidney function (>6%) in scintigraphy was observed in two of the 15 patients after the surgery. The time of surgery decreased from 140 (range 85–185) min in Group 1 to 125 (range 100–150) min in Group 2 (p < 0.05). Conclusions: Laparoscopic heminephrectomy is connected to the learning curve. Most complications occurred in the first 16 operations. With increasing experience, the time of operation decreased. In patients with reflux to the upper pole, referred for upper pole heminephrectomy, it is necessary to consider the removal of the ureter to the level of the vesicoureteral junction.